Micro-Slab Coil Design for Hyperpolarized Metabolic Flux Analysis in Multiple Samples - Geonhui Lee; Thomas Ruan; Claudia Wong; Kofi Deh; Alli Abolarin; Alexander Correa; Kayvan R. Keshari; Sangmoo Jeong (Bioengineering, 2022)
Abnormal metabolism is a hallmark of cancer cells. Accumulating evidence suggests that metabolic changes are likely to occur before other cellular responses in cancer cells upon drug treatment. Therefore, the metabolic activity or flux in cancer cells could be a potent biomarker for cancer detection and treatment monitoring. Magnetic resonance (MR)-based sensing technologies have been developed with hyperpolarized molecules for real-time flux analysis, but they still suffer from low sensitivity and throughput. To address this limitation, we have developed an innovative miniaturized MR coil, termed micro-slab MR coil, for simultaneous analysis of metabolic flux in multiple samples. Combining this approach with hyperpolarized probes, we were able to quantify the pyruvate-to-lactate flux in two different leukemic cell lines in a non-destructive manner, simultaneously. Further, we were able to rapidly assess flux changes with drug treatment in a single hyperpolarization experiment. This new multi-sample system has the potential to transform our ability to assess metabolic dynamics at scale.